Der poetische Formismus Tytus Czyżewskis Ein literarischer Ansatz der fruehen polnischen Avantgarde und sein mitteleuropaeischer Kontext - Eberharter, Markus (Slavistische Beitraege, 2004)
In this work an attempt is made to describe formism in terms of Tytuz Czyżewski's poetry as an independent poetic approach. The starting point is the aesthetic writings on the visual art of Chwistek and Witkacy. On the basis of central ideas developed in them, the formistic can be made more recognizable and serve as a basis for the interpretation of Czyżewski's poems. Thus, their analysis deals with problems of a form-oriented art, the relationship between form and content in the literary work of art, and the relationship between art and extra-artistic reality, with which the formists' intention is to dissolve art or literature from their mimetic function and to emphasize the individual processing of the outer world by the artist. Such understood poetic formism stands for a thoroughly original literary approach, which apart from Expressionism and Futurism can be regarded as characteristic of the early Polish avant-garde. A comparison of formism with parallel currents of the Hungarian and Czech avant-garde completes this work.